Cat and Mouse Optimizer: A Bio-Inspired Feature Selection Algorithm for IoV Cybersecurity - Raavi Deepthi (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Feature selection critically impacts thecomputational efficiency and detection accuracy of intrusion detection systems in resource-constrained